Visualizing the strongly reshaped skyrmion Hall effect in multilayer wire devices - Anthony K. C. Tan (Nature Portfolio, 2021)
Skyrmions - nanoscale, topological spin textures - are promising elements for next-generation computing due to their efficient coupling to currents in racetrack devices. Here, Tan et al. examine over 20,000 instances of current induced skyrmion motion to unveil a comprehensive picture of skyrmion dynamics across currents and fields.